2014
DOI: 10.15835/nbha4219331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drought Tolerance in Safflower Genotypes Based on Drought Tolerance indices

Abstract: Among the different environmental stresses, drought is the constraint that induces a highly negative effect on crop production. In order to identify drought tolerant genotypes in safflower, an experiment was conducted in a randomized complete block design with three replications under rainfed and irrigated conditions during 2011-2012 cropping season at Agricultural and Natural Resources Research Center of West Azerbaijan, Iran. Seven drought resistance indices including Stress Tolerance Index (STI), Tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
7
12
0
1
Order By: Relevance
“…Thus, based on SI, it seems that plant breeders can select lines with high yield and suitable agronomic traits for drought-prone condition. The ability of the STI, MP and GMP indices to identify genotypes suitably under both conditions observed in this study is consistent with the results reported by Nouri et al (2011) with durum wheat, Farshadfar et al (2012) with bread wheat, Naghavi et al (2013) with maize, Khalili et al (2014) with safflower, and Poursiahbidi and Pour-Aboughadareh (2013) with chick pea.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, based on SI, it seems that plant breeders can select lines with high yield and suitable agronomic traits for drought-prone condition. The ability of the STI, MP and GMP indices to identify genotypes suitably under both conditions observed in this study is consistent with the results reported by Nouri et al (2011) with durum wheat, Farshadfar et al (2012) with bread wheat, Naghavi et al (2013) with maize, Khalili et al (2014) with safflower, and Poursiahbidi and Pour-Aboughadareh (2013) with chick pea.…”
Section: Discussionsupporting
confidence: 92%
“…Three indices (YI, YSI, and RSI) can be used to evaluate genotypic stability in both stressful and non‐stressful conditions. These indices are based on tolerance or susceptibility of genotypes, and have been used in many crops, including bread wheat (Sardouei‐Nasab et al., ), durum wheat (Etminan et al., ), barley (Khalili et al., ), safflower (Khalili et al., ), chickpea (Pour‐Siabidi and Pour‐Aboughadareh, ), and potato (Cabello et al., ). YSI and RSI produced similar ranking patterns in the characterization of tolerant genotypes, with G55, G47, G69, G71, and G46 having the highest values.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The YI, YSI, and RSI are based on tolerance or susceptibility of genotypes and can be used in genotypic stability studies under both stressful and nonstressful conditions. These indices have been used in several crops, including wheat (Etminan et al., 2019), barley ( Hordeum L.; Khalili et al., 2016), safflower ( Carthamus tinctorius L.; Khalili et al., 2014) and potato ( Solanum tuberosum L.; Cabello, Monneveux, Mendiburu, & Bonierbale, 2013). Therefore, the breeders should take advantage of these indices on the basis of stress severity of the genotypes in their breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…A range of stress tolerance indices have been proposed and utilized for the evaluation and screening of tolerant genotypes under stressed conditions (Farshadfar, Mohammadi, Farshadfar, & Dabiri, 2013; Fernandez, 1992). For example, drought susceptibility index (DSI), stress tolerance Index (STI), and geometric mean productivity (GMP) index are efficient for identifying genotypes with good performance to both stressed and nonstressed conditions (Khalili, Pour‐Aboughadareh, & Naghavi, 2016; Khalili, Pour‐Aboughadareh, Naghavi, & Mohammad‐Amini, 2014). In a study, Akçura, Partigoç, and Kaya (2011) used stress susceptibility index (SSI), STI, yield stability index (YSI), and Harmonic mean (HM) to identify drought‐tolerant bread wheat ( Triticum aestivum ) genotypes, and suggested that SSI is a useful indicator for wheat breeding when the stress is severe while STI and HM are beneficial when the stress is less severe.…”
Section: Introductionmentioning
confidence: 99%